Informed consent to the receipt and use of human cellular material: juristic and ethical regulation - D. V. Stambolsky; E. V. Bryzgalina; A. Yu. Efimenko; K. Yu. Alasania; E. M. Shkomova; S. M. Gavrilenko; T. A. Varkhotov; S. T. Matskeplishvili (Российский кардиологический журнал, 2018)
Further progress in medicine is closely related to the clinical introduction of regenerative technologies, including cell therapy. Presented article covers the ethical and legal status of obtaining an informed consent from donors of cell material. The manuscript defines specific functions of such informed consent related to the features of research object and possibilities of its further use. The recommended content of the informed consent from cell material donors is determined in the context of global trends as well as guidelines for obtaining the consent. Existing difficulties and contradictions while developing an informed consent are presented